Surgical safety distances in the infratemporal fossa: three-dimensional measurement study. Issue 5 (May 2015) - Guo, Y.X.; Sun, Z.P.; Liu, X.J.; Bhandari, K.; Guo, C.B.
Abstract The wedge-shaped infratemporal fossa is a constricted space and has long been a surgical challenge, mainly due to difficulties in access. Three-dimensional (3D) reconstruction of the skull, internal carotid artery (ICA), and internal jugular vein (IJV) was carried out using enhanced computed tomography (CT) data, to measure the safety distances in relation to infratemporal fossa surgery. Fifty enhanced CT datasets were selected to reconstruct 3D images by segmentation technique. The anatomical routes of the ICA, IJV, and the styloid process (SP) were observed. The following were measured: SP length, height of the pterygoid plates (PP height), distances from the pterygoid process (antero-inferior and anterosuperior border) to the leading edge of the ICA (PP–ICA (inferior), PP–ICA (superior)), and distance between the most prominent point of the zygomatic arch and the medial pterygoid plate (Zyg–MPP). The mean measurements of SP length, PP height, and the distances PP–ICA (inferior), PP–ICA (superior), and Zyg–MPP were 30.64 mm, 26.61 mm, 31.16 mm, 34.37 mm, and 51.37 mm, respectively. No significant differences were observed by age group, except the distance of PP–ICA (inferior) on the left side. In centres without intraoperative navigation facilities, proper knowledge of the anatomy, particularly of bony landmarks and the safe distances to nearby neurovascular structures, can provide useful information to ensure safe operations.